Efektifitas Cuka Kayu sebagai Pestisida Nabati dalam Pengendalian Hama Crocidolomia Pavonana dan Zat Perangsang Tumbuh pada Sawi - Nunung Ambarwati; Subagiya Subagiya; YV Pardjo NS (Universitas Sebelas Maret, 2013)
Cabbage caterpillar pests (Crocidolomia pavonana) is one of the main obstacles inhibiting the production both in quality and quantity. Control is generally done with chemical pesticides that can harm the environment and humans. Wood vinegar is an agricultural waste that is used to increase the quantity and quality of mustard plant. This study aims to determine the effectiveness of wood vinegar as a botanical pesticide in the mustard plant and the PGR and the most effective concentration. Research using completely randomized design with 7 degree treatment laboratory tests (mortality, biology, kemampua eating) and 8 standard treatment field test (the intensity of pest attack, plant height, leaf number and weight of mustard plant), repeated 3 times. The results showed that wood vinegar is not effective as a pesticide plant pest control C.pavonana the mustard. Wood vinegar speed up the life cycle C. pavonana. Wood Vinegar can help to enhance and augment leaf mustard plant so that it can be effective as an aphrodisiac mustard plant grows. The greater the concentration of a given wood vinegar, increased growth (both height and number of leaves of mustard plant).